Penerapan Arsitektur Tradisional Bali Pada Bangunan Hospitality - Putra, I Wayan Yogik Adnyana; Putra, I Dewa Gede; Utami, I Gusti Ayu Canny; Utami, Ni Wayan Ardiarani (Jurnal Arsitektur Universitas Udayana; Vol 13 No 01 (2025): Jurnal Arsitektur, Universitas Udayana, 2025)
This research aims to identify and analyze the design of hospitality buildings in Bali, focusing on the application of traditional and modern architectural elements that reflect local culture. In the context of globalization, architecture in Bali faces the challenge of maintaining its identity amid increasingly modern design trends. The research method used is qualitative, including a comparative analysis of Potato Head Studios, Adiwana Jeevalokha Hotel, and The Saraswati with a locality approach. The results indicate that the design of hospitality buildings in Bali is dominated by principles of harmony with nature and sustainability. The use of local materials and environmentally friendly construction techniques are important aspects in creating attractive and sustainable spaces. Additionally, the application of Balinese cultural philosophies, such as the concepts of sanga mandala and Tri Angga, is clearly reflected in spatial arrangements and building forms. This study aims to identify the application of traditional Balinese architecture in hospitality buildings, focusing on the interaction between traditional and modern architecture that reflects local culture. Keywords: Hospitality Design, Bali Architecture, Cultural Identity